Fodor's Kaua'i. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to Kaua'i in the Hawaiian Islands, with maps and information on hotels and restaurants, shopping and entertainment, and interesting tourist sites.
"Pullout map inside"--Cover.
Maps on inside cover.
Includes bibliographical references and index.
Young Adult
Keywords: Kauai (Hawaii) -- Guidebooks; Kauai (Hawaii) -- Guidebooks